(untitled) (Research, Society and Development, 2020)
Streamflow regularization is essential when the water demand is greater than the minimum streamflow. This makes it necessary to accumulate excesses to meet periods in which natural water availability is less than the demand for abstraction. In this context, the objective of the work was to regionalize the streamflow regularization curve for the Juruena river basin in order to subsidize projects for granting and dimensioning reservoirs. A dimensionless streamflow smoothing curve was generated for seven stream gaging station. Then the potential model was adjusted to the data of the curves in order to regionalize them. The proposed regionalization equations have precision and accuracy and can be used as a basis for streamflow regulation projects for irrigation, public supply and electricity generation.